Getting on the Same Page Identifying Goals for Technology Use in Early Childhood Education - Daugherty, Lindsay (RAND Corporation, 2014)
Technology use among young children is increasingly a fact of life, but debates about the role of technology in early childhood education (ECE) are ongoing, with some stakeholders unwilling to accept any role for technology in ECE. Based on findings from a forum and review of the literature, the authors offer ways to move past that debate and suggest several core goals that might be adopted to guide technology use in ECE.